Upaya Hukum Penyelesaian Wanprestasi Perjanjian Peminjaman Modal Menurut Kitab Undang Undang Hukum Perdata (Studi Putusan Mahkamah Agung No. 3220 K/Pdt/2001.) - Aflah, Aura Alfitrah; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2024)
The reason for this study is to figure out how to determine the Default on Functioning Capital Credit Loaning Arrangement as per the Common Code that defaults and what are the elements that cause default. By utilizing standardizing juridical examination strategies, to be specific the strategy for legitimate materials acquired from the library or regulations. In the assortment of legitimate materials the writer utilizes sources from regulations, related books, articles, reports, as well as other logical works. The problem approach employing a statutory approach leads to the conclusion that the debtor or party who committed the default must indemnify for the acts he committed. This research is normative legal research. What's more, it is beneficial that the gatherings to the consent to figure out the privileges and commitments of every one of them.